Socialization and Mentoring of Project-Based Learning Model for PJOK Teachers in Palembang City - Yusfi , Herri; Bayu , Wahyu Indra; Syafuddin; Destriani; Nanda, Fitri Agung; Rasyono, Rasyono (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Socialization and guidance to the community regarding project-based learning models in Pendidikan Jasmani Olahraga Kesehatan (PJOK) learning in Palembang City in collaboration with partners, namely MGMP PJOK in Palembang City. The target audience in this service activity is PJOK teachers in Palembang City totaling 40 people. The method of implementing activities is by socialization and guidance on the project-based learning model. As for the results of this community service activity, the pretest results are 72% of teachers are still confused and do not understand how a good and appropriate project-based learning model is applied in PJOK learning in Palembang city. PJOK teachers in Palembang City do not know about the application and structure of running a project-based learning model, only about 38% have known and tried to apply the learning model but in the question and answer session during the pre-test the teacher was also confused about applying the project in PJOK learning. After socialization and guidance on the project-based learning model has increased 100% of teachers understand and understand the concepts of project-based learning that are well applied in PJOK learning Palembang City. The conclusion in this community service activity is that it has a good impact on PJOK teachers in Palembang City who understand and understand the project-based learning model to improve PJOK learning outcomes in Palembang City